Adsorption Behavior of Cr(VI) on Al-Fe Cointercalated Bentonite. Issue 8 (16th November 2016) - Cao, Chun-Yan; Liang, Cheng-Hua; Yin, Yan; Du, Li-Yu
Abstract : An efficient Al-Fe cointercalated bentonite composite material (Al-Fe/Bent) which is capable of removing hexavalent chromium [Cr(VI)] from aqueous solutions was prepared. The batch experiment studies were conducted to evaluate the adsorption performance of Cr(VI) contained in aqueous solution. The XRD results showed the spacing of layers of bentonite was increased due to the aluminum and iron polycation intercalated into the layer of bentonite. The removal rate of Cr(VI) from the aqueous solution could be up 87.4% under the condition of the dosage of Al-Fe/Bent 8 g/L, pH 4, and a contact time of 60 min. The equilibrium data fitted well to the Freundlich model. The adsorption process could be well described by the pseudosecond order kinetic model.